2021
DOI: 10.3390/jcm10153404
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning Is Safe and May Reduce the Rate of Intubation in Selected COVID-19 Patients Receiving High-Flow Nasal Oxygen Therapy

Abstract: Background: Patients with COVID-19 may experience hypoxemic Acute Respiratory Failure (hARF) requiring O2-therapy by High-Flow Nasal Cannula (HFNO). Although Prone Positioning (PP) may improve oxygenation in COVID-19 non-intubated patients, the results on its clinical efficacy are controversial. The present study aims to prospectively investigate whether PP may reduce the need for endotracheal intubation (ETI) in patients with COVID-19 receiving HFNO. Methods: All consecutive unselected adult patients with bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The search yielded thirteen relevant studies which fitted with our purpose ( Ehrmann et al, 2021 , Ferrando et al, 2020 , Ibarra-Estrada et al, 2022 , Jouffroy et al, 2021 , Kaur et al, 2021 , Kucukdemirci-Kaya et al, 2022 , COVIDPREG Study Group, 2022 , Vanderbilt Learning Healthcare System Platform Investigators, 2022 , PROFLO Study Group, 2021 , Tu et al, 2020 , Vianello et al, 2021 , Xu et al, 2020 , Yang et al, 2020 ). The search and selection strategies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search yielded thirteen relevant studies which fitted with our purpose ( Ehrmann et al, 2021 , Ferrando et al, 2020 , Ibarra-Estrada et al, 2022 , Jouffroy et al, 2021 , Kaur et al, 2021 , Kucukdemirci-Kaya et al, 2022 , COVIDPREG Study Group, 2022 , Vanderbilt Learning Healthcare System Platform Investigators, 2022 , PROFLO Study Group, 2021 , Tu et al, 2020 , Vianello et al, 2021 , Xu et al, 2020 , Yang et al, 2020 ). The search and selection strategies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Jouffroy et al ( Jouffroy et al, 2021 ) France 40 (37 HFNO/ APP) Admission, not specified. NA 3-6 h, 2 times/ day NA No effects on intubation (HR 0.96) or 28-day mortality rates (HR 0.51) Vianello et al ( Vianello et al, 2021 ) Italy 93 Admission, not specified. FiO2 0.21-1.0 flow up to 60 L/min adjusted to maintain SpO2>93% >2 h, 2 times/ day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 , 29 ] Efforts have been undertaken to reduce the need for intubation due to its association with higher mortality and the use of scarce resources in the pandemic setting. [ 2 , 7 ] Early observational studies have shown controversial effects of APP on the need for intubation, [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [30] , [31] , [32] ] while early randomized controlled studies with small sample sizes have not been able to detect the differences in intubation by APP. [ [17] , [18] , [19] , [20] , 33 ] However, from observational studies, it is interesting to note that a significant reduction in the need for intubation through APP implementation has been found in most of the studies in which patients received predominantly high-flow nasal cannula (HFNC).…”
Section: Introductionmentioning
confidence: 99%
“…[ [17] , [18] , [19] , [20] , 33 ] However, from observational studies, it is interesting to note that a significant reduction in the need for intubation through APP implementation has been found in most of the studies in which patients received predominantly high-flow nasal cannula (HFNC). [ 11 , [30] , [31] , [32] ] The largest randomized evidence published as an international multi-centered meta-trial, including patients hospitalized with acute hypoxemic respiratory failure due to COVID-19 pneumonia and requiring HFNC treatment, has demonstrated that APP significantly reduced the risk of intubation by 7%. [21] Moreover, meta-analyses and systematic reviews of non-randomized controlled studies have also shown the effect of APP on reducing the risk of intubation, [22] except for a meta-analysis conducted by Pavlov et al [25] at early pandemic, and including only observational studies.…”
Section: Introductionmentioning
confidence: 99%